Flexor-Pronator Mass Training Exercises Selectively Activate Forearm Musculature - Takumi Fukunaga; Connor Fedge; Timothy Tyler; Michael Mullaney; Brandon Schmitt; Karl Orishimo; Malachy McHugh; Stephen Nicholas (North American Sports Medicine Institute, 2023)
# Purpose/Hypothesis The flexor-pronator mass of the forearm contributes dynamic stability to the medial elbow. Training this muscle group is essential for overhead athletes, however, there is lack of evidence supporting use of training exercises. The purpose of this study was to measure the extent of EMG activity of the flexor pronator musculature during two distinct forearm strengthening exercises using resistance bands. It was hypothesized that two exercises would elicit at least moderate level of muscle activity, but the activation would be different in the pronator versus the flexor muscles. # Materials/Methods 10 healthy subjects (all males, age 36±12 years) were included. Surface EMG activity was measured on three muscles of the dominant-side forearm: flexor carpi ulnaris (FCP), flexor digitorum superficialis (FDS), and pronator teres (PT). After measurement of maximal voluntary contraction (MVC) for each muscle, subjects performed wrist ulnar deviation and forearm pronation exercises using elastic band resistance. Resistance was set to elicit moderate exertion (5/10 on the Borg CR10 scale). Order of exercise was randomized and three repetitions of each exercise were performed. Mean peak EMG activity in each muscle across repetitions during the eccentric phase of each exercise was calculated and expressed as a percentage of MVC. Moderate level of activity was defined as 21% of MVC or higher. Peak normalized EMG activity in each muscle was compared using two-way (exercise x muscle) repeated-measures ANOVA with post-hoc pairwise comparisons if a significant interaction was found. # Results There was an exercise by muscle interaction effect (p\<0.001). The ulnar deviation exercise selectively activated FCU (40.3%) versus FDS (19.5%, p=0.009) and PT (21.5%, p=0.022). Conversely, the pronation exercise selectively activated FDS (63.8%, p=0.002) and PT (73.0%, p=0.001) versus FDS (27.4%). # Conclusion The ulnar deviation and pronation exercises using elastic band resistance studied targeted and activated the flexor-pronator mass musculature. The ulnar deviation and pronation exercises using elastic band resistance are practical and effective means of training the flexor-pronator mass. These exercises can be readily prescribed to athletes and patients as part of their arm care program.